2022
DOI: 10.1111/ijfs.15408
|View full text |Cite
|
Sign up to set email alerts
|

A review on instant controlled pressure drop technology – a strategic tool for extraction of bioactive compounds

Abstract: Summary Bioactive compounds are the naturally derived extra‐nutritional components with diversified arrangement and functionality, which makes them a promising source for the fabrication of functional foods, nutraceuticals and food additives. Extraction of these compounds by traditional techniques is a cumbersome process, which yields product with compromised quality and poor efficiency besides huge investment in terms of energy and time. This urges an acute need to develop an improved method that ensures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Ultrasound-assisted extraction can also increase the availability of bioactive compounds in food. It is likely that ultrasound assistance is a good alternative method to improve the yield and bioavailability of compounds compared to the heat reflux method [66].…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound-assisted extraction can also increase the availability of bioactive compounds in food. It is likely that ultrasound assistance is a good alternative method to improve the yield and bioavailability of compounds compared to the heat reflux method [66].…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
“…The stability of bioactive compounds is an important criterion for bioavailability. Studies have observed that sonicated juice had lower oxygen levels, which was a favorable environment for carotenoid retention [66]. Ultrasonic technology is also useful in inhibiting the enzymatic browning process.…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
See 1 more Smart Citation